-4(k-17)=0

Simple and best practice solution for -4(k-17)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(k-17)=0 equation:


Simplifying
-4(k + -17) = 0

Reorder the terms:
-4(-17 + k) = 0
(-17 * -4 + k * -4) = 0
(68 + -4k) = 0

Solving
68 + -4k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-68' to each side of the equation.
68 + -68 + -4k = 0 + -68

Combine like terms: 68 + -68 = 0
0 + -4k = 0 + -68
-4k = 0 + -68

Combine like terms: 0 + -68 = -68
-4k = -68

Divide each side by '-4'.
k = 17

Simplifying
k = 17

See similar equations:

| 0.08x+0.11(3x+37000)=18290 | | 12d+6=9d | | -9-4K=-1-5k | | 1x/2x-1/10x=1/5-1/4 | | 4p=6p-16 | | -3(m-12)=-12 | | 81*.15= | | 12+c=-2c | | -4(x-3)=x | | -16k=-15k-16 | | -4n+5=13 | | -4+5=13 | | 8x/20x=9/20 | | 6x-6+x=4x+8 | | -9x+2.6+(-x)+(-12.8)= | | 2x+9-3x=12 | | z^2+16z+7=0 | | X+3y+3z=10 | | x/x^2=0 | | (Ab+b-c+6)+(3ab-b+c-6)= | | 8a-4(-5a-2)=24a | | 6u+8=21 | | 2y-24=26 | | 1/3s=-2 | | 10-2/5x=-3 | | 5e+6pd+5d-7ed+7= | | 10-2/5x=3 | | 1/2(13f/5 | | 4-1/2v=-4 | | 2.5+-3.5x=-32x+-48 | | 4-1/2v=4 | | 12+4pd-2p+6pd= |

Equations solver categories